ANALISIS MATEMATIS PENGARUH LOKASI RUMAH TERHADAP HARGA JUAL, LUAS RUMAH DAN JUMLAH KAMAR DENGAN MANOVA - Annisa Nur Afifah Kusuma Sayekti; A’yunin Sofro; Danang Ariyanto (LPPM Universitas Bina Bangsa, 2024)
A house is a building that functions as a residence or residence and a means of family development (Law No. 4 of 1992). Every community needs a house as a necessity. With so many people needing a place to live, house construction often occurs. As time goes by, many houses have been built. From the number of houses, they can be classified into several groups, one of the classifications is based on the location where the house was built. The classification of houses based on the location where the house was built is classified into 3, namely houses in rural areas, urban areas and suburban areas. Based on this classification, data on houses being sold on the kaggle.com website was taken. From this data, the characteristics of the houses in the 3 groups can be described. The characteristics chosen are selling price, house area, and number of bedrooms. Using this data, carry out analysis using the MANOVA method. The aim of this research is to determine the influence between house location and selling price, house area and number of rooms